Type specimens of family Annonaceae Juss. kept in herbaria of St. Petersburg State University (LECB) and St. Petersburg State Forest University (KFTA), St. Petersburg (Russia) - Byalt, Vyacheslav; Potokin, Alexandr; Bubyreva, Valentina (Biological Communications, 2014)
The article continues a series of publications on the study of collection of typical specimens kept in herbaria of St. Petersburg State University (LECB) and I. P. Borodin Herbarium of St. Petersburg State Forest Technical University (KFTA). Critical study of herbarium collections of family Annonaceae Juss. in LECB and KFTA reveals 78 authentic specimens that belong to 59 species and 26 genera (Alphonsea Hook. f. & Thomson, Anaxagorea St. Hil., Ararocarpus Scheff., Artabotrys R. Br., Asimina Adans., Coelocaryon Warb., Cyathocalyx Champ. ex Hook. f. & Thomson, Goniothalamus (Blume) Hook. f. & Thomson, Guatteria Ruiz & Pav., Marsypopetalum Scheff., Melodorum Lour., Mezzettia Becc., Mitrephora Hook. f. & Thomson, Monoon Miq., Parartabotrys Miq., Piptostigma Oliv., Polyalthia Blume, Popowia Endl., Pseuduvaria Miq., Rhopalocarpus Teijsm. & Binn. ex Miq., Trivalvaria Miq., Unona L. f., Uva Kuntze, Uvaria L., Uvariastrum Engl. & Diels and Xylopia L.). Although the KFTA is a relatively small herbarium (a total of about 180 000 specimens), it houses a large number of authentic specimens (64 specimens for 59 species of 26 genera of the family) usually poorly represented in the Russian herbaria, which is a noteworthy fact. The collection of LECB contains 14 specimens for 14 species of 9 genera of this family, which is also very important. Refs 22.